2012
DOI: 10.1016/j.ijgo.2012.07.027
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health awareness among educated young women in Egypt

Abstract: Awareness of RH is poor in Egypt, even among young women attending institutions of higher education. The present study not only highlights the persistent need for the ongoing RH information programs, but may also provide policy makers with data that will inform new strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 5 publications
2
21
1
Order By: Relevance
“…The reference lists of the selected publications were screened for additional papers of interest, and citation tracking of these papers was used. There were nine questionnaire survey-based studies from five different countries in MENA: Turkey [5-12] Iran [7,8] Egypt [11] Lebanon [13] the United Arab Emirates [9] and Saudi Arabia [10]. There was a general lack of knowledge and limited awareness of SRH matters.…”
Section: Introductionmentioning
confidence: 99%
“…The reference lists of the selected publications were screened for additional papers of interest, and citation tracking of these papers was used. There were nine questionnaire survey-based studies from five different countries in MENA: Turkey [5-12] Iran [7,8] Egypt [11] Lebanon [13] the United Arab Emirates [9] and Saudi Arabia [10]. There was a general lack of knowledge and limited awareness of SRH matters.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that 40% of studied people not heard about folic acid supplementation before pregnancy to prevent neural tube defects. Most previous researches regarding this point implement their studies on general women and not specify a group of people as university students [1,6,13].…”
Section: Significance Of the Studymentioning
confidence: 99%
“…Preconception health means identifying and understanding of current health status of woman and risk factors that may effect on woman or her fetus health in her potential pregnancy. Issues that may involve in preconception health may put fetus in a danger include woman's health condition, medical and obstetrics history, genetic factors, taking of any drugs, exposure to environmental toxins and lifestyle [1,2,3,4].…”
Section: Introductionmentioning
confidence: 99%
“…19 Women's awareness of their reproductive anatomy has been associated with high education level of both the women and their parents, exposure to media outlets and living near healthcare facilities. [20][21][22] Further, several studies have found that educating women on their cervix and cervical cancer significantly increased cervical cancer screening rates more than two-fold. 18,19,[23][24][25][26][27][28][29] Simply put, giving women access to accurate information and a comprehensive education on their sexual anatomy can significantly improve their understanding of sexual and reproductive health.…”
Section: Introductionmentioning
confidence: 99%